PENERAPAN METODE GALLERY WALK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA DI SEKOLAH DASAR - Maisaroh; Fadhilaturrahmi; Nurhaswinda; Yenni Fitra Surya; Afriza Rahma Rani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed at describing the increase of student creative thinking ability in mathematics learning through Gallery Walk method at the fourth grade of State Elementary School 009 Pulau Jambu. It was classroom action research. The subjects of this research were a teacher and 21 students. The objects were Gallery Walk method and creative thinking ability. This research was conducted for two cycles, and every cycle comprised two meetings. Observation, test, and documentation were the techniques of collecting data. The technique of analyzing data was qualitative descriptive analysis with percentage. Based on the research findings and data analyses, student creative thinking ability was still low before the action were on very uncreative category. After the improvement action with Gallery Walk method was conducted in the first cycle, student creative thinking ability increased 75 was on uncreative category. In the second cycle, student creative thinking ability increased again 85 were on creative category. Therefore, it could be concluded that the learning with Gallery Walk method could increase student creative thinking ability in mathematics learning at the fourth grade of State Elementary School 009 Pulau Jambu.